2017
DOI: 10.1177/2041669517724807
|View full text |Cite
|
Sign up to set email alerts
|

When Does Maluma/Takete Fail? Two Key Failures and a Meta-Analysis Suggest That Phonology and Phonotactics Matter

Abstract: Eighty-seven years ago, Köhler reported that the majority of students picked the same answer in a quiz: Which novel word form (‘maluma’ or ‘takete’) went best with which abstract line drawing (one curved, one angular). Others have consistently shown the effect in a variety of contexts, with only one reported failure by Rogers and Ross. In the spirit of transparency, we report our own failure in the same journal. In our study, speakers of Syuba, from the Himalaya in Nepal, do not show a preference when matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 43 publications
3
104
0
1
Order By: Relevance
“…They found that speakers of all languages judged [a] to be larger than [i], hinting at the universality of this pattern (though see Diffloth, 1994); on the other hand, Japanese speakers judged [o] to be larger than [a], whereas Chinese and Korean speakers showed the opposite pattern, and English speakers did not show a substantial difference between the two vowels. To take another example, the takete ‐ maluma effect (Köhler, 1947) has been shown to hold across many languages (Styles & Gawne, 2017), but it fails in Songe (Rogers & Ross, 1975) and Syuba (Styles & Gawne, 2017). Based on a meta‐analysis of the previous studies on the takete‐maluma effect, Styles and Gawne tentatively propose that it fails to hold if the stimuli violate phonotactic restrictions of the target language.…”
Section: Common Issues and Shared Interestsmentioning
confidence: 99%
“…They found that speakers of all languages judged [a] to be larger than [i], hinting at the universality of this pattern (though see Diffloth, 1994); on the other hand, Japanese speakers judged [o] to be larger than [a], whereas Chinese and Korean speakers showed the opposite pattern, and English speakers did not show a substantial difference between the two vowels. To take another example, the takete ‐ maluma effect (Köhler, 1947) has been shown to hold across many languages (Styles & Gawne, 2017), but it fails in Songe (Rogers & Ross, 1975) and Syuba (Styles & Gawne, 2017). Based on a meta‐analysis of the previous studies on the takete‐maluma effect, Styles and Gawne tentatively propose that it fails to hold if the stimuli violate phonotactic restrictions of the target language.…”
Section: Common Issues and Shared Interestsmentioning
confidence: 99%
“…For example, it may well be the case that sound-symbolic guessing for consonant glyphs may be stronger than it is for vowel glyphs, a finding that would be consistent with experimental pseudoword shape-matching tasks [ 33 , 36 ]. As it stands, the choice of two highly contrastive ‘bare’ vowels allows the smallest unit of comparison that is utterable, implemented using high prevalence, highly contrastive phonemes that are canonical for these kinds of effects [ 56 ]. Despite the narrow phonological range, this study provides proof of concept for further (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has begun to document cross-cultural differences in linguistic sound symbolism [ 28 , 56 ], as well as in audio–visual cross-modal mappings related to linguistic metaphor [ 46 , 57 , 58 ]. For instance, in at least two cases, the well-known matches between pseudoword pairs like bouba/kiki and maluma/takete do not show the expected pattern of audio–visual correspondence in languages where the test items do not match the sound structure of the language (see [ 56 ] for extended discussion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was decided based on the amount of early blind participants we could reach and the strength of the effect. Although the experiment had only 4 trials, the bouba-kiki effect is know to be fairly strong, with ~80-90% of participants choosing the typical shape-sound associations (Styles & Gawne, 2017), suggesting that it should be highly replicable, even with small samples. Moreover, we substantially increased the number of early blind participants (from 6 to 30) compared to the experiment that we intended to conceptually replicate .…”
Section: Participantsmentioning
confidence: 99%